Sistem pencalonan hadiah akademik pelajar UTM berkonsepkan SBK hybrid - Yusoff, Ahmad Riza'Ain (2008)
An excellent student in studies and co-curiculum commonly will be honoured during graduation ceremony. The student evaluation for this award usually came across problem if there will be more than one assessor arguing about the matters. The purpose of this studies is to develop a system that can support evaluation process and improve consistency to pick a right candidate for right award. Decision Support System (DSS) techniques have been chose to improve the effectiveness of the current evaluation process. Research have been made on Hybrid DSS (HDSS) combined Web-based DSS, Model based DSS, Data based DSS and Delphi principles of fasilitator. The current and to be model have been model using UML techniques. Beside that, this new system will be build using RAD methodology. This system also will be develop with simple interfaces and user friendly function to assist user with simple function along with latest technology.